ESTUDO QUÍMICO DA PRÓPOLIS DOS CAMPOS GERAIS DO PARANÁ - Cordeiro, Adriana Rute (2013)
This study aimed to develop methods for obtaining extracts for the isolation and chemical analysis of propolis using two samples from the region known as “Campos Gerais do Paraná”. One of the studied propolis samples was produced in the district of Ipiranga and another in the municipality of Ponta Grossa. The utilized general fractionation method allowed obtaining from the same sample the essential oils and then the aqueous extracts and various organic fractions containing chemical components of several polarities. The analyses of the essential oils showed that both samples of propolis contain several components found in Baccharis dracunculifolia, known as vassoura or alecrim do campo, indicating that these are similar to those of green propolis produced in southeastern Brazil. The analyses also demonstrated the presence of phenol compounds such as flavonoids and caffeoylquinic acids, pointing once again that the botanical origin of both propolis includes the alecrim do campo. The analyses of essential oils originating from Ipiranga propolis sample indicated spathulenol and (E)-nerolidol as the main components, while the one acquired in Ponta Grossa showed high proportions of two substances containing aromatic rings in their structures, 2,6-di-t-butyl-p-cresol and benzyl benzoate. The two sesquiterpene alcohols spathulenol and (E)-nerolidol are commonly found in essential oils from B. dracunculifolia and appear in propolis from Ponta Grossa in low percentages, while the two mentioned aromatic compounds are not commonly found in the genus Baccharis. The various analyses of extracts and isolates showed that two aromatic acids may be considered as marker substances for both samples of propolis. The para-hydroxycinnamic acid seemed to be characteristic of propolis from Ipiranga, while the benzoic acid could be considered typical of the sample from Ponta Grossa. Atomic absorption spectrometry analyses that were conducted with both studied propolis did not indicate neither high levels of essential minerals nor the presence of heavy metals, and this fact represents a guarantee that producers have been working in clean environments.